Penerapan Prinsip yang Sama Dalam Investasi Terhadap Hak Asasi Investasi Lokal - Ratu Ratna Korompot (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe application of the same principle or the application of non-discrimination against foreign investors to come to invest in Indonesia, increase economic growth in Indonesia, the application of the Investment Law no. 25 of 2007 in article 3 letter d. However, what about local Indonesian investors as TKI, the arrival of TKA which reached 36.17 percent, most of whom were unskilled laborers, which should have occurred in the transfer of technology to potential workers who have the ability to work skills, did not occur, as well as highly discriminatory wages locally 100,000 and 800,000 TKA. There is a waiver of the 1945 Constitution, Article 33 and Article 27. The presence of the Job Creation Law can reduce the gap in investment. Answering local labor problems and clarifying the same principle without discrimination. Business companies must respect human rights. The responsibility of business companies to respect human rights refers to internationally recognized human rights. Keywords: Local Investors; The Principle of Equality in Investment; Local Workers. AbstrakPenerapan prinsip yang sama atau pemberlakuan non diskriminasi terhadap para investor asing untuk datang menanamkan modal ke Indonesia, meningkatkan pertumbuhan ekonomi di Indonesia, penerapan UU Penanaman Modal no 25 tahun 2007 pada pasal 3 huruf d. Namun bagaimana dengan investor lokal Indonesia sebagai TKI, kedatatangan TKA yang mencapai 36, 17% , yang umumnya adalah buruh kasar, yang mestinya terjadi alih teknologi terhap tenaga kerja potensial yang memiliki kemampuan ketermpilan kerja, tidak terjadi, serta pengupahan yang sangat diskriminasi lokal 100.000 dan 800.000 TKA. Adanya pengabaian terhadap UUD 1945, pasal 33 dan pasal 27. hadirnya UU Cipta Kerja dapat mengurangi kesenjangan dalam investasi. Menjawab permasalahan tenaga kerja lokal dan lebih memperjelas tentang prinsip yang sama tanpa diskriminasi. Perusahaan bisnis harus menghormati hak asasi manusia.Tanggung jawab perusahaan bisnis untuk menghormati hak asasi manusia mengacu pada internasional hak asasi manusia yang diakui.Kata Kunci: Investor Lokal; Prinsip Persamaan Dalam Investasi; Tenaga Kerja Lokal.